Food policies and their implications on overweight and obesity trends in selected countries in the Near East and North Africa region - Abay, Kibrom A.; Ibrahim, Hosam; Breisinger, Clemens; Bayasgalanbat, Nomindelger (International Food Policy Research Institute, 2020)
Regional and global trends in body weight show that the Near East and North Africa (NENA) region countries, especially the Gulf Cooperation Council (GCC) member countries, have the highest average body mass index and highest rates of overweight and obesity in the world. There exist several explanations that expound the high rates of overweight and obesity in most NENA countries, including the nutrition transition, urbanization, changes in lifestyle, and consequent reduction of physical activities. This study examines the implication of food policies, mainly trade and government food subsidies, on evolving nutritional transitions and associated body weight outcomes. We examine the evolution of trade (food) policies, food systems, and body weight outcomes across selected countries in the NENA region – Egypt, Jordan, and Iraq. In particular, we investigate the implications of important trade (food) policies in shaping diets and food systems as well as their implications on public health outcomes, mainly the rising levels of overweight and obesity in the NENA region. We provide a simple conceptual framework through which trade policies (tariff rates) and domestic government food policies (subsidies) may affect food systems and nutritional outcomes. An important and innovative feature of this study is that it compiles several macro- and micro-level datasets that allow both macro and micro-level analyses of the evolution of trade (food) policies and associated obesity trends. This approach helps to at least partly overcome the data scarcity that complicates rigorous policy research in the NENA region.